(untitled) (Journal of Parents and Teachers, 1996)
Juvenile delinquency reflects social injustices and adverse economic conditions, with many juveniles living in extreme poverty and being victims of exploitation. Rehabilitation institutions often fail to provide adequate support, perpetuating the cycle of crime. It is essential to address these realities through a comprehensive approach that includes education and decent living conditions.